Effects of sex steroids on thymic epithelium and thymocyte development - Taves, Matthew D.; Ashwell, Jonathan D. (Frontiers in Immunology, 2022)
Sex steroid hormones have major effects on the thymus. Age-related increases in androgens and estrogens and pregnancy-induced increases in progestins all cause dramatic thymic atrophy. Atrophy can also be induced by treatment with exogenous sex steroids and reversed by ablation of endogenous sex steroids. Although these observations are frequently touted as evidence of steroid lymphotoxicity, they are often driven by steroid signaling in thymic epithelial cells (TEC), which are highly steroid responsive. Here, we outline the effects of sex steroids on the thymus and T cell development. We focus on studies that have examined steroid signaling in vivo, aiming to emphasize the actions of endogenous steroids which, via TEC, have remarkable programming effects on the TCR repertoire. Due to the dramatic effects of steroids on TEC, especially thymic involution, the direct effects of sex steroid signaling in thymocytes are less well understood. We outline studies that could be important in addressing these possibilities, and highlight suggestive findings of sex steroid generation within the thymus itself.